Pengembangan dan Pengujian Aplikasi Computer Based Test dengan Menggunakan Algoritme Fisher-Yates Shuffle sebagai Pengacakan Soal - Abdullah, Naufal Fachry (Journal of Computer Science and Engineering (JCSE), 2023)
Many studies have confirmed that the application of information technology has helped humans to be more efficient in carrying out their activities. The daily repetition at the 5 Brebes State High School, using the conventional method, with the question of the written examination, it poses some challenges such as, teachers take quite a long time to correct the answers, since one teacher can teach up to 7 classes, another obstacle when examining is cheating by students during the examination. This research aims to develop and evaluate a Computer Based Test based on a Website, thus making it easier for teachers to correct students' answers, which are dual-choice, because the results of the correction will automatically exit the system and the application of the Fisher-Yates Shuffle algorithm will be able, minimizing the level of student fraud, because questions are spotted for each student. System development will use the Waterfall method with phases, analysis, design, program code making, testing. Based on the random permutation calculation of an existing question, when there are 15 questions but only show 10 questions, it results in permutations of 360.360 models, then the probability calculation that has been done yields 0,00832%, the chances of 30 students getting the same sequence of topics of 15 existing questions. Based on the results of the validation test, the comparison of the correction time for one class with the issue of double selection, which previously took 15 minutes, while using a Computer Based Test of 32 seconds. While the level of cheating is minimized, because the sequence of matters presented to each student will be different.